Health indicators as moderators of occupational commitment and nurses' intention to leave. Issue 1 (15th July 2019) - Asakura, Kyoko; Asakura, Takashi; Satoh, Miho; Watanabe, Ikue; Hara, Yukari
Abstract: Aim: This study examined the hypothesis that health indicators moderate the relationship between occupational commitment and intention to leave among nurses, using a large sample in Japan. Methods: A self‐administered questionnaire was distributed to all registered nurses ( N = 11, 171) working in group hospitals in western Japan in 2014. The questionnaire evaluated intention to leave, occupational commitment, psychological distress, cumulative fatigue, and demographic variables. After a preliminary analysis of the bivariate and multivariate associations between variables and intention to leave, we tested the interactions between occupational commitment and health indicators on intention to leave. Results: Of the 5, 768 returned questionnaires, data from 5, 505 (49.3%) participants were analyzed. Participants' mean age was 36.27 years (SD = 10.37). Most (95.14%) were women. According to a generalized estimating equation, the interaction of continuance occupational commitment and cumulative fatigue was significantly related to intention to leave ( b = −0.0055). Additionally, the interaction of affective occupational commitment and psychological distress was significantly related to intention to leave ( b = 0.0079). Conclusions: This study clarified that the relationship between occupational commitment and intention to leave was robust for nurses in good health. Interventions aimed at reducing fatigue and improving psychological distress should be implemented to prevent the protective effects of occupational commitment on nurses' intention to leave from being compromised.